CYBER SECURITY AWARENESS SYSTEM - YOGESH SHELOKAR; PROF SACHIN VYAWHARE (International Journal of Innovations in Engineering Research and Technology, 2021)
This Project attempts to measure the level of cyber security parental awareness to protect their children, by means of survey reports among parents of students aged 17 and below. A quantitative data analysis was performed using Project software and interpreted based on the distribution of positions. A mixture of general profiling of respondents and descriptive statistics were used during the analysis method. Any findings to this project would mean an increased attention to the suggested Cyber Parenting Model in order to establish the factors that affect Internet safety at home. Early exposure to parental awareness would aid in opening up knowledge about cyber security among parents.